Epidemiology Profile of Stage IV Ovarian Cancer in Dharmais National Cancer Hospital: An Observational Study - Tadjoedin, Hilman; Suryana, Kresna Dharma; Hanafi, Widyorini Lestari Hutami; Kunigara, Manika Putri; Shiba, Alyssa Fairudz (http://dharmais.co.id/, 2025)
Background: Stage IV ovarian cancer showed a low 5-year survival rate, around 31%. Regrettably, the unclear symptoms and the ineffectiveness of early detection result in many patients being diagnosed with stage IV. Moreover, establishing a stage IV diagnosis is challenging and tricky. This study aims to provide a comprehensive overview of the clinical, laboratory, histopathological, and survival characteristics of stage IV ovarian cancer patients.Method: A cross-sectional study with a descriptive observational design, 100 of 1520 subjects gathered from the Cancer Registry of Dharmais National Cancer Hospital between January 2018 and December 2022, conducted on stage IV ovarian cancer patients who were not accompanied by primary cancer at other sites.Results: Among the 100 study subjects, 76.0% were aged 40–60 years, with a median age of 49.5 years. Most had a normal nutritional status (39.0%) or were underweight (34.0%). Comorbidities were present in 40.0% of the subjects, with hypertension being the most common (57.5%). The initial symptoms were abdominal enlargement in 74.0% of subjects, with 43.0% reporting shortness of breath. Laboratory examinations revealed that the majority had hemoglobin levels 10 mg/dL (90.0%), serum creatinine levels 1.2 mg/dL (90.0%), and D-Dimer levels 2000 ng/ mL (69.0%). Histopathological analysis identified high-grade serous carcinoma (HGSC) in 24.0% and clear cell carcinoma in 19.0% of subjects. The most common metastatic sites were the pleura (44.0%), liver (41.0%), and lungs (25.0%). Around 48.0% and 41.0% had surgery only and surgery with adjuvant chemotherapy, respectively. The majority of the outcomes (91.0%) indicated that patients with stage IV ovarian cancer did not survive and the median survival among the subjects was 4 months.Conclusion: The majority of stage IV ovarian cancer patients were aged 40–60 years, with abdominal enlargement as the initial symptoms, elevated D-Dimer levels, HGSC as the predominant histopathological type, and a high mortality rate as the outcome. Further research is recommended to explore additional variables and analyze factors contributing to mortali